Interpolative Kannan- Meir-Keeler type contraction - KARAPINAR, Erdal (Advances in the theory of nonlinear analysis and its applications, 2021)
In this short manuscript, we revisit the renowned contraction’s of Meir-Keeler by involving the interpolation theory in the context of complete metric space. We provide a simple example to illustrate the validity of the observed result